Influence Of Government Accounting Information Systems, Implementation of Government Accounting Standards, Human Resource Competence, and Internal Control Systems as Moderator Variables on the Quality of Regional Government Financial Reports in the Study of Buton Selatan District - Hamza, La Ode Firman; Sabir, Sabir; Aswan, Andi (Pancasila International Journal of Applied Social Science, 2023)
This study analyzes the influence of Accounting Information Systems, Application of Accounting Standards, and Competence of Human Resources on the quality of the financial reports of the Government of South Buton Regency. In addition, this study also explores the moderating role of the Internal Control System on the relationship between these factors and the quality of financial reports. Data is collected through a survey of respondents who are involved in the process of accounting and financial reporting. The results of the analysis show that these three factors have a significant and positive influence on the quality of financial reports. In addition, the findings also reveal that the Internal Control System has an important role as a moderating factor that can strengthen the positive relationship between these factors and the quality of financial reports. This study provides a holistic view of the factors that influence the quality of financial reports in local government and highlights the importance of information management, application of accounting standards, human resource development, and the role of the internal control system in ensuring the accuracy, relevance and integrity of financial reports.